2016
DOI: 10.1080/07370652.2016.1210697
|View full text |Cite
|
Sign up to set email alerts
|

Safer and Performing Energetic Materials Based on Polyaniline-Doped Nanocomposites

Abstract: Nanothermites, combining a fuel with an oxidizer at the nanoscale, represent a class of energetic material that has been attracting increasing attention over the past decade. This intensive interest is due to their tuneable pyrotechnic performance, making the materials promising candidates for ordnance applications. However, the extreme mechanical and electrostatic sensitivities of energetic composites make handling them hazardous. In this study, a realistic desensitisation method is suggested via the addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 27 publications
3
50
1
Order By: Relevance
“…The use of polyaniline conducting polymer (PAni) as an additive is particularly interesting and promising, as reported by Gibot et al . For example, when added to an Al/WO 3 nanothermite, the PAni additive allowed the considerable mitigation of the electrostatic sensitivity (with the friction threshold increasing) while preserving an acceptable reactivity for the energetic mixture considered . In this work, the conducting polyaniline nanofibers were separately synthesized before they were added to the fuel/oxidizer nanocomposite.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…The use of polyaniline conducting polymer (PAni) as an additive is particularly interesting and promising, as reported by Gibot et al . For example, when added to an Al/WO 3 nanothermite, the PAni additive allowed the considerable mitigation of the electrostatic sensitivity (with the friction threshold increasing) while preserving an acceptable reactivity for the energetic mixture considered . In this work, the conducting polyaniline nanofibers were separately synthesized before they were added to the fuel/oxidizer nanocomposite.…”
Section: Introductionmentioning
confidence: 93%
“…In the literature, the mitigation of the sensitivity of the nanothermites is addressed either by acting on the fuel (especially when aluminum is used), modifying the particle size, and changing the alumina/aluminum ratio constituting the fuel particles, or inserting a third compound (desensitizer) within the conventional binary fuel/oxidizer energetic mixture . With regards to the use of an additive, different kinds of carbonaceous compounds (carbon black, graphite, nanotubes, nanofibers, graphene, and nanodiamonds), polymers (polytetrafluoroethylene and polyaniline) and inorganic species (molybdenum sulfide) have been tested, and many of them have a positive effect on the electrostatic discharge (spark) desensitization as well as a lesser effect toward mechanical stress such as friction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis is supported by flame propagation velocity measurements in tubes, which showed that the combustion front travels at 351 m/s and 510 m/s in Na 2 SO 4 /Al and Na 2 S 2 O 8 /Al, respectively [43]. Tubes used for studying the flame propagation velocities in nanothermites or hybrid compositions are made of a transparent matter such as poly (methyl methacrylate) [45], polycarbonate [56,59] or glass [101]. The ideal internal channel diameter is of 3 to 5 mm, which has the triple-edge advantage to facilitate the tube loading, to reach a flame propagation velocity close its maximal value [102] and to limit the amount of composition needed.…”
Section: Understanding the Reactionsmentioning
confidence: 75%